Program refactoring in the presence of preprocessor directives [recurso electrónico] - Garrido, Alejandra (2005)
The C preprocessor is heavily used in C programs because it provides useful and even necessary additions to the C language. Since preprocessor directives are not part of C, they are removed before parsing and program analysis take place, during the phase called preprocessing. In the context of refactoring, it is inappropriate to remove preprocessor directives: if changes are applied on the preprocessed version of a program, it may not be possible to recover the un-preprocessed version. This means that after refactoring, all the source code would be contained in a single unit, targeted to a single con¯guration and without preprocessor macros.This thesis describes a novel approach to preserve preprocessor directives during parsing and program analysis, and integrate them in the program representations. Furthermore, it illustrates how the program representations are used during refactor- ing and how transformations preserve preprocessor directives. Additionally, the semantics of the C preprocessor are formally speci¯ed, and the results of implementing this approach in a refactoring tool for C, CRefactory, are presented.
Introduction -- Related works- The C Preprocessor -- Pseudo-Preprocessing in CRefactory -- Program Representations that Integrate C and Cpp -- Applying Refactoring -- Quantitative Evaluation of CRefactory -- Conclusions -- Appendix A Maude Specification of Cpp -- Appendix B Maude Specification of P-Cpp -- Appendix C C Grammar with Cpp extensions -- Appendix D Source Code of Examples -- References -- Author's Biography. -- Formato de archivo: PDF. -- Disponible también en línea (Cons. 17/03/2009)
Tesis (Doctor of Philosophy in Computer Science) - University of Illinois at Urbana-Champaign. Technical Report No. UIUCDCS-R-2005-2617. --
Keywords: DIAGNÓSTICO MÉDICO; PREPROCESADORES; MULTIPROCESADORES